Psychological Well-Being of School Teachers: The Role of Adjustment and Marital Status - Kumari, Madhumita; Singh, Lav Kumar (Journal of Neonatal Surgery, 2025)
The present study examined the psychological well-being of school teachers in relation to their adjustment and marital status. A descriptive, comparative, and correlational research design was adopted. The sample comprised 300 school teachers (191 married and 109 unmarried) selected from government and private secondary and senior secondary schools of Darbhanga district, Bihar, using a purposive-cum-incidental sampling technique. Psychological well-being was assessed using the Psychological Well-Being Scale (PWBS) developed by Devendra Singh Sisodia and Pooja Choudhary, while adjustment was measured using the Mangal Teacher Adjustment Inventory (MTAI) developed by Dr S. K. Mangal. The collected data were analysed using descriptive statistics, independent samples t-test, and Pearson's product-moment correlation. The findings revealed no significant differences between married and unmarried teachers in overall psychological well-being and adjustment. However, married teachers scored significantly higher on the interpersonal relations dimension of psychological well-being. Furthermore, adjustment was found to be significantly and negatively correlated with psychological well-being and all its dimensions, indicating that better-adjusted teachers experienced higher psychological well-being. The study concludes that adjustment is a significant correlate of teachers' psychological well-being, whereas marital status has a limited influence. The findings underscore the importance of promoting adjustment and psychological well-being through supportive school environments and teacher well-being programmes....